Mau Mau and the Kikuyu - Leakey, L. S. B. (Louis Seymour Bazett), 1903-1972 (Routledge library editions. Anthropology and ethnography., 2004)
This widely-acclaimed book on a troubled period of Kenyan history summarizes some of the more important Kikuyu customs, and a discussion of their break-down under the impact of European civilization. This discussion illustrates why and how the Mau Mau came into being and how the situation could be improved so that peace could once again come to Kenya.